2005
DOI: 10.1080/09638280400006515
|View full text |Cite
|
Sign up to set email alerts
|

The disablement process: Factors associated with progression of disability and recovery in French elderly people

Abstract: These findings confirm the independent contribution of each group of variables in the disablement process and stress their different impact on progression of disability or on recovery from different grades of disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
71
1
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 60 publications
9
71
1
7
Order By: Relevance
“…With regard to the observed association between polypharmacy and WFS, few studies that observed this issue were identified in the literature, and the present results are consistent with some of them [40][41][42][43] . Pérès et al 43 observed a positive association between the progression of disability and the number of medications ( four or more) in a cohort of older adults (65 years and over). High medication intake may constitute a measure of the individual's health status 43 .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…With regard to the observed association between polypharmacy and WFS, few studies that observed this issue were identified in the literature, and the present results are consistent with some of them [40][41][42][43] . Pérès et al 43 observed a positive association between the progression of disability and the number of medications ( four or more) in a cohort of older adults (65 years and over). High medication intake may constitute a measure of the individual's health status 43 .…”
Section: Discussionsupporting
confidence: 79%
“…Pérès et al 43 observed a positive association between the progression of disability and the number of medications ( four or more) in a cohort of older adults (65 years and over). High medication intake may constitute a measure of the individual's health status 43 . Furthermore, it may reflect aspects other than co-morbidities, such as the severity of the co-morbidity or the probability of iatrogenesis and/or the use of inadequate medications 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Female gender and older age appear on a recurring basis as risk factors for functional disability in the majority of studies 16,19,20 and the present study is no exception. Women have a higher life expectancy than men and pass a greater proportion of their life with functional disability; moreover, when affected by this condition, they live for a longer period with dependency 21 .…”
Section: Discussionmentioning
confidence: 61%
“…In a French population study, 46.1% of the elderly presented mild disability, while 28.5% presented moderate to severe disability 19 . One study conducted in Brazil involving 33.786 elderly individuals verified that the most prevalent profile was healthy elderly individuals (50.8%), followed by mild (33.7%) and severe disability (15.5%) 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the disablement pathway model in some detail (22,9,29,28); however, there has been limited investigation utilizing a culturally diverse sample. Although these studies demonstrated the utility of the disablement pathway model, the demographic characteristics of the study sample justifies the purpose of examining the contribution of physical function, pain, and dyspnea to ADL disability in a more culturally diverse sample of older adults.…”
Section: Discussionmentioning
confidence: 99%